2014
DOI: 10.1063/1.4893775
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic performance and characteristic of vortex structures for Darrieus wind turbine. I. Numerical method and aerodynamic performance

Abstract: Articles you may be interested inAerodynamic performance and characteristic of vortex structures for Darrieus wind turbine. II. The relationship between vortex structure and aerodynamic performance J. Renewable Sustainable Energy 6, 043135 (2014); 10.1063/1.4893776 Unsteady vortex lattice method coupled with a linear aeroelastic model for horizontal axis wind turbine J. Renewable Sustainable Energy 6, 042006 (2014); 10.1063/1.4890830 3D stall delay effect modeling and aerodynamic analysis of swept-blade wind t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…The results showed that the previous shedding vortex could affect the development of a new vortex and the vortex intensity increased with the increase of the angle of attack. Sun et al [12] in 2014 and Li et al [13] in 2017 investigated the wind velocity distribution of flow fields around the VAWT at different TSRs by experimental measurements. In their studies, a wide range of low wind velocities was found from the internal region to the near-wake of the wind turbine.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the previous shedding vortex could affect the development of a new vortex and the vortex intensity increased with the increase of the angle of attack. Sun et al [12] in 2014 and Li et al [13] in 2017 investigated the wind velocity distribution of flow fields around the VAWT at different TSRs by experimental measurements. In their studies, a wide range of low wind velocities was found from the internal region to the near-wake of the wind turbine.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, and at the maintenance terms, turbines will be stationary and the static torques (C ms ), static thrusts (C xs ), and static tangential forces (C Ts ) will impact the several parts and probably failures will occur. Figure 11 introduces a rapprochement between the turbines with several Present work (CFD) Castelli et al [5] (CFD) Hashem and Mohamed- [18] (CFD) Mohamed et al [12] (CFD) Sun et al [22] (CFD) Mohamed [7] Figure 9: Present CFD study versus the experimental results of [5] and other CFD results for a Darrieus turbines [5,7,12,18,22]. sectional pro le airfoils (NACA 0021, LS413, and S1046) for that aerodynamic forces coe cient.…”
Section: Resultsmentioning
confidence: 99%
“…e aerodynamic rapprochement and proximity of power coefficients C p between the current model and experimental results have been published by Castelli et al [5]. It was carried out as well as other CFD outputs [5,7,12,18,22] as shown in Figure 9. e comparison was quantitative and qualitative.…”
Section: Methodology and Model Validationmentioning
confidence: 99%
“…Fig16 The comparsion of calculated data with literature results and experiment values for VAWT It is observed that Sun et al[64] using one equation turbulence model (Spalart-Allmaras, S-A) produced large discrepancy relative to experimental data, especially at low to medium TSRs. The two-equation realizable k-ε model used by Castelli et al[48], although capable of replicating the shape of the experimental curve and…”
mentioning
confidence: 80%